ASSESSMENT OF MOTIVATION FOR GOING IN FOR SPORTS AND FITNESS OF STUDENTS OF PHYSICAL CULTURE AND SPORTS UNIVERSITIES USING ATHLETICS EXERCISES - Kostyuchenko, V.F.; Lutkovsky, V.E.; Sukhareva, S.M.; Vrublevsky, E.P. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to identify the features of the technical and physical readiness of students as a result of mastering the discipline "Theory and methods of teaching the types of athletics" taking into account the direction of their special motivation. Methods and structure of the study. Students (full-time and part-time) who specialize in various sports and study at the 1st year of university (n=356) took part in the scientific experiment. The motives that prompted them to go in for sports and receive higher professional education were established. Technical readiness in the types of athletics was determined using an expert assessment method using a point-rating system. The level of physical fitness was assessed using the standard results shown in the types of athletics. Motivation was determined by analyzing a questionnaire survey. Results and conclusions. It was revealed that the level of physical fitness among full-time students of both sexes, in comparison with the part-time form, is significantly higher (р≤0.05). Full-time students master the technical types of track and field exercises more effectively. Full-time students have a higher level of professional motivation, and part-time students are purposefully motivated to receive higher education.